Effect Of Pulsed Electro Magnetic Field (Pemf) Exposure On Hatchability Performance Of Japanese Quail Hatching Eggs - Pandian, C.; Omprakash, A.V.; Selvan , S.T.; Sundaresan , A. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A study was conducted to analyze the hatchability performance of Japanese quail breeder hatching eggs at Poultry Research Station, Tamil Nadu Veterinary and Animal Sciences University (TANUVAS), Chennai – 51. A total of 33792 Japanese quail breeder hatching eggs with 6 settings were divided in to four equal groups of each 8448 eggs as T1, T2, T3 (Treatment group) and T4 (Control group). The treatment groups hatching eggs viz, T1,T2 and T3 were exposed to PEMF at 1 Hz frequency with 1500 nT intensity for 18, 12 and 6 hours respectively at 180C and 80 per cent relative humidity. The control eggs were stored at the same temperature and humidity but kept unexposed to the PEMF. After bringing into room temperature for one hour, the eggs were incubated under optimum temperature and humidity in setter and hatcher. The total and fertile hatchability performance showed highly significant (P< 0.01) difference between treatment and control groups. There were significant differences (P<0.05) observed for mean per cent embryonic mortality, mean per cent dead in germ and dead in shell between treatment and control group. Mean per cent fertility did not show any significant difference between treatments and control group. This study concluded that PEMF exposure could be a useful tool to improve the hatching performance of Japanese quail.